Teachers for rural schools – a challenge for South Africa - Pierre du Plessis; Raj Mestry (South African Journal of Education, 2019)
Poverty is rife in many African countries and this has serious implications for the provision of quality education. Rural schools face severe challenges that are unique to their environment. A lack of parental interest in children’s education, insufficient funding from the state, a lack of resources, underqualified teachers, and multi-grade teaching are some of the barriers to effective education. These challenges can be attributed to numerous sources, from within school structures and from the external environment, including local communities and education authorities. After 25 years of democracy, educational standards and learner performance in rural schooling has shown little improvement. This study illustrates the complexity and inter-connectedness of the problems faced by teachers in South African rural schools. Using qualitative research within the interpretivist paradigm, this article explores the perceptions and experiences of teachers in rural schools located in White River in the Mpumalanga province. This grounded-theory research focuses on effective teaching and learning. The findings reveal that most rural schools do not have water, sanitation, or electricity, and classrooms are in a terrible state. These issues have serious implications for effective teaching and learning.